The Effect of Corrosion Inhibitors on the Corrosion Behavior of Ductile Cast Iron - Jing Liu; Bingqin Wang; Tianqi Chen; Lianjun Hao; Jun Wu; Chao Liu (Metals)
Based on actual service environment parameters, this experiment investigated the change in the corrosion rate of nodular cast iron (DCI) in an environment containing organic (triethanolamine phosphate, PTEA) and inorganic (hexametaphosphate, SHMP) inhibitors, and analyzed the effects of both inhibitors and the pH value of the solution on the corrosion behavior of DCI. Additionally, a variable flow rate device was used to conduct immersion tests, enabling the accurate evaluation of the materials’ corrosion resistance in an actual service environment. After a certain period, the corrosion of the DCI surface was observed, and the weight loss corrosion rate of the materials was calculated to analyze the differences in corrosion resistance under varying environmental parameters. It was found that the inhibitory effect of both inhibitors on DCI increased with the immersion time, and the inhibitory effect of the SHMP inhibitor was more pronounced under alkaline conditions. Based on the electrochemical and flow rate immersion test results, it can be concluded that, in the solution environment used in this experiment, the inhibitory effect of the SHMP inhibitor on DCI is stronger than that of the PTEA inhibitor.